UNDERSTANDING HOW A MUSLIM’S WIDOW LIFE CHANGES AS A CHRONIC KIDNEY DISEASE PATIENT - Yuzana Mohd Yusop (Yayasan Pendidikan Medika Indonesia, 2023)
Many studies for chronic kidney patients are being conducted around the world, but they all focus on a variety of factors that have an impact on the patients' day-to-day lives. When a patient starts dialysis, they may face a range of changes and challenges. Patients' usual routines were significantly modified because of the treatment. Most of the studies being conducted among dialysis Muslim patients focus on certain issues such as fasting, and emotion distracted due to the situation. In this case study, the aim was to explore the living experiences of a Muslim widow who was a dialysis and chronic kidney disease patient. This is one of the 16 participants who were interviewed semi-structured based on the researchers' criteria for Muslim dialysis patients. Only one of them was chosen for this case study. All of the interviews, including this one, were taped, transcribed, analysed, and categorised into themes. She had talked about how she had been diagnosed as a patient with chronic kidney disease and the difficulties she had faced along the way. She was a chronic kidney patient, having dialysis three times a week, which dramatically altered her everyday routine. The circumstances had a significant impact on her life. She took the initiative to learn more about dietary requirements because she had to watch what she ate and drank. Considering the circumstances, she becomes more devoted to Allah Almighty as she looks up information about ibadah that is pertinent to her situation as a Muslim. She apparently accepted the situations that drastically altered her life and treated them as a challenge in life. Researchers concluded that in this case study, how a chronic kidney patients handle problems from dialysis regular changes throughout her life, would be made public.